The Law Applicable to Environmental Damage in European Private International Law - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The paper contains an analysis of choice of law rules in the field of non-contractual liability for damage caused to environment in national legislations of European countries as well as in Private International Law of the European Union. Before the adoption of Regulation of the European Parliament and of the Council on the law applicable to non-contractual obligations (Rome II), special choice of law rules for environmental torts existed in a small number of European national legal orders. This is the fact that gives the rule contained in Article 7 of the Rome II Regulation a particular importance. From the Serbian Private International Law perspective, the significance of that provision is highlighted by the fact that the working draft of the new Serbian Private International Law Act has strictly followed the choice of law rule envisaged by the European legislator for environmental damage. For that reason, a significant part of the paper is dedicated to analysis of said rule, to its interpretation and potential problems which its application could create.
Keywords: environmental damage; non-contractual obligations; applicable law; the Rome II Regulation; choice of law rules